Enhancing SDT Efficacy of Doxorubicin‐Loaded Sonosensitizer Micelles to Overcome Resistance of Cancer Therapy by Optimizing Acoustic Parameters - Zhuoran Gong; Deshang Hou; Yunxue Xu; Mengxuan Wang; Shiyin Lin; Yingjuan Zheng; Zhifei Dai (Aggregate)
ABSTRACT Tumor drug resistance has been reported to be associated with drug efflux in tumor cells. Recently, a noninvasive and safe mechanism, sonodynamic therapy (SDT), has been proposed to be an oxidative stress strategy to potentially overcome drug efflux, but with efficacy limitation. Herein, we propose a systematic strategy for optimizing SDT, especially revealing the key role of acoustics parameters acting in SDT efficiency. A doxorubicin (DOX)‐loaded sonosensitive micelle (DPM) mediated “sono‐force” combination (chemotherapy and sonodynamic) therapy strategy, named DPCSTs, which was designed for amplifying SDT to augment oxidative stress to overcome drug efflux and induce robust long‐term inhibition of tumor development by optimized acoustic parameters. The sub‐10 nm size DPM enhanced tumor targeting and renal clearance. Meanwhile, another important component, doxorubicin, significantly suppressed residual tumors (78.6%) due to “sono‐force” augmented oxidative stress reversing drug efflux, finally leading to long‐term tumor development limitation in vivo. It is the first time to propose a systematic strategy for optimizing SDT regimens to overcome resistance, which can synergize with chemotherapy to exert long‐term tumor development inhibition. We believe that this work will advance SDT‐related research to a new level, and improve our understanding of overcoming resistance of targeted cancer therapy.